(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
Essential oils are rich sources of biologically active compounds possessing diverse medicinal properties. These form integral part of a number of herbal formulations. The most challenging part of commercialization of herbal formulation is to ensure consistency in quality from batch to batch. The aim of present study was to develop a validated gas chromatographic method based on quality by design (QbD) for routine quality control purpose. A blend of essential oils possessing synergistic carminative properties was formulated in oily base. Ajowan oil, cardamom oil, caraway oil, coriander and fennel oil were selected for development of formulation. A gas chromatography method was developed for routine quality control purpose of the developed formulation by quality by design techniques (QbD). Each oil was characterized making use of a marker compound which was linalool for coriander oil, cineol for cardamom oil, anethol for fennel oil, carvone for caraway oil, thymol for ajowan oil and menthol for peppermint oil. Marker compound was characterized using mass spectroscopy. Chromatography method was established by quality by design approach and validated based on ICH guidelines.